Cash, COVID-19 and the prospects for a Canadian digital dollar - Walter Engert; Kim P. Huynh (Bank of Canada, 2022)
We provide an analysis of cash trends in Canada before and during the COVID-19 pandemic. Focusing on the pandemic period, we explore the implications on demand for, use of and access to cash. We find that cash demand has been strong pre-pandemic and increased sharply during the pandemic. While cash use fell initially due to the decreased number of in-person shopping opportunities, it recovered as containment measures eased. We explore the potential two scenarios for issuance of central bank digital currency or Canadian digital dollar. We discuss the Canadian experience in maintaining cash as an efficient and accessible method of payment and store of value.
Keywords: C; C1; C12; C9; E; E4; O; O5; O54; 330; Bank notes; Central bank research; Coronavirus disease (COVID-19); Digital currenciesand fintech; Econometric and statistical methods